(untitled) (CIPEEX, 2023)
The aging process is associated with impairments in strength, lean mass (LM), cardiovascular health (CVH), and cardiorespiratory health (CRH), due to metabolic, hemodynamic, and body composition changes in the elderly. The implications of these changes within the aging process can have their effects mitigated through nutritional intervention and physical training. To test this hypothesis, a randomized clinical trial was determined to be conducted at the Evangelical University of Goiás (UniEVANGÉLICA), where elderly volunteers (60 to 85 years old) will be randomized (n = 40/group) into groups (1) Control (no protein supplementation and no physical training), group (2) Supplementation (only protein supplementation), group (3) Training (only physical training), and group (4) Protein supplementation + Physical training (physical training + protein supplementation). The supplementation protocol and the training protocol will be carried out for 3 months, and the evaluations will take place before the start of the protocol and after 3 months. Numerous cardiovascular, pulmonary, immunological, renal, muscular, and hematological parameters will be evaluated. The analyses will be expressed as mean and standard deviation. A significance level of p≤0.05 will be adopted for comparisons made in the paired T-test and for multiparametric analyses. It is expected that the effects of the resistance training protocol and protein supplementation, together or separately, will significantly improve the parameters described above, bringing positive results for the participants.